RANCANG BANGUN ALAT PEMOTONG PAKAN TERNAK BABI DENGAN MENGGUNAKAN PENGGERAK MOTOR LISTRIK - Rendi Rendi; Yus Witdarko; Yosefina Mangera (Musamus AE Featuring Journal, 2022)
The aim of the research is to produce a pig feed cutting machine with an electric motor drive. This study used an experimental method by making and testing pig feed cutting tools with one type of blade using an electric motor drive. The materials used in testing the tool were water spinaches, sweet potato leaves, and banana stems. The calculations performed are the effective capacity of the tool and the efficiency of the tool. Tests were carried out on 3 types of feed ingredients, each of which was repeated 3 times with an electric motor rotation of 1400 rpm. The results showed that the pig feed cutting machine with an electric motor had the specifications: overall height 110 cm, front width 45 cm, side width 50 cm side inlet funnel height 17 cm and width 10 cm, funnel bottom exit height 23 cm and width 17 cm, the width of the electric motor mount is 45 cm and the length is 28 cm. The cutting blade uses a grass cutter blade with a blade length of 305 mm and a blade thickness of 1.6 mm. The effective capacity of the tool for cutting water spinaches (162 kg/hour), sweet potato leaves (162 kg/hour), banana stem (163.8 kg/hour). The efficiency of the tool for cutting kale and sweet potato leaves was the same, namely 90%, while the efficiency of the tool for cutting banana stems was 91.1%.